Factors Affecting Risk Attitude and Investors’ Happiness of Newly Employed Individuals - Linge, Ashish A.; Jiwani, Adil; Kakde, Baldeo B. (Indian Journal of Finance, 2024)
Purpose : This study aimed to evaluate the impact of risk attitude and holding risk-free and risky assets on investors’ happiness. It also aimed to study investors’ demographic differences in risk attitude and happiness. Evaluation of the impact of age and family size of investors on their risk attitudes was another aim of this study. Methodology : This study evaluated the impact of three independent variables, viz, holding risk-free assets, holding risky assets, and risk attitude on one dependent variable, i.e., investors’ happiness with an investment decision. A sample survey of 409 newly employed individuals having work experience of less than five years was conducted in Vidarbha, India. The data was analyzed by using multiple regression and MANOVA using the SPSS software. Findings : Investor satisfaction has been demonstrated to have a modest, positive, and significant association with risk attitude. The contentment of investors was significantly impacted by both holding risk-free and risky assets. It was discovered that there were significant gender differences in investors’ happiness. Nonetheless, there was no discernible variation in investors’ levels of enjoyment based on their income or marital status. Practical Implications : This research has significant implications for managers in understanding the various facets of the investment behavior of youth and demographic differences in their investment behavior. Financial advisors would be able to plan their sales pitches by referring to the results. Originality : In contrast to earlier studies on behavioral finance, the current work examined the topics of investment behavior in the Indian setting, with a focus on risk attitude, involvement in the financial market, and satisfaction of recently hired people.